Pengelolaan layanan perpustakaan khusus: Pengalaman praktis di Perpustakaan DPR RI - Diny Nurafnie (Dedicated: Journal of Community Services (Pengabdian kepada Masyarakat), 2026)
The House of Representatives (DPR RI) Library is a specialized library that provides services to members of parliament and the general public, serving as a center for information, archives, and research on development and political issues in Indonesia. In its implementation, the library serves as a liaison institution and compiles accurate records of the DPR RI's legislative activities for the public. Through the MSIB program, students with a background in Library and Information Science have the opportunity to intern as Assistant Librarians and carry out direct management activities at the DPR RI library, while also gaining experience related to the management of a special library. This program covers various tasks that support library operations, including circulation services, assisting users in accessing information, promoting the library, and processing library materials, both print and digital. The method used in this article is qualitative, with direct practice, observation, and documentation as data collection methods. The results of this internship provide increased competency in mastering technical skills (library collection processing) and non-technical skills (communication, time management, collaboration) in the library. In addition, the MSIB program provides an overview of the special services offered by the DPR RI Library for library users (e-kliping, e-paper, SiPinter, RAMEN, etc.), as well as insight into the operational mechanisms at the DPR RI Library and the importance of collaboration in information management and public services.